Determinants de ladoption des technologies de transformation de ligname: cas de la transformation en cossettes et en farine au nord de la Cote Divoire - Monney, R.F.; Coulibaly, S.; Sylla, K.; Diallo, S.S.; Nkamleu, G.B. (2009)
Yam processing technology adoption: the case of yam chip flour production in northern of Côte d’Ivoire. This Journal Article provides an empirical analysis of yam processing technology adoption. The study, one of the few in the field of yams which analyses the processing technology adoption, explores the links between social, cultural, and professional farmers and adoption of processing technologies. Its main objective is to identify factors that influence yam chip and flour production and the processing technology adoption in the north of Cote d’Ivoire. More specifically, the study involved households in the area covered by the project “Enhancement of yam: yam chip system” executed from 1998 to 2001. A Logit regression model was used to identify the adoption’s reasons. Factors influencing the decision to adopt are extension service, age and belonging to the caste of farmers. The guidance offered to producers of yam influences significantly and positively the likelihood of adoption. In the same case, age and caste are significant and improve the likelihood of adoption.